THE EXPRESSION OF THE FIGURATIVE WORDS AND PHRASES IN THE ENGLISH, UZBEK AND RUSSIAN LANGUAGES - Ibragimovna, Gadoeva Mavlyuda; Xakimovna, Umurova Xushvaxt; Askarovna, Shukurova Madina; Ikromovich, Akramov Izzatulla; Ilxomjonovna, Jumaeva Ozoda (International Journal of Psychosocial Rehabilitation, 2020)
-This article is dedicated to the expression of the figurative words and phrases in the English, Uzbek and Russian languages.